e-Shape : interactive mobile application to learning basic shape for autism kids - Farah Farhanah, Ahmad Zunaidi (Universiti Malaysia Sarawak (UNIMAS), 2014)
Autism is a developmental disability caused by neurological disorders that affect substantially the normal function of the brain. Therefore, learning and teaching methods to children according to ability and level of development of their brain. Nowadays, with increasingly advanced technology, learning how children can be produced with more attractive and easier for their learning process. Android platform on mobile phones is one medium or learning process how to replace the existing manual methods. This application is built for autistic children to learn basic shapes like square, circle, oval, rectangle, diamond and triangle. This application is designed and developed with an interactive graphics and easy to learn to attract children with autism. This application has also been tested on children with autism to understand the effectiveness of this application in their learning process.